Engaging the hands, heads, and hearts in a medical simulation informal learning environment. Issue 6 (10th December 2020) - Tal, Tali; Dallashe, Sameer
Abstract: We investigated the characteristics of a medical simulation‐based informal learning environment (MSBE) of a science center—an environment not yet studied—to understand its uniqueness and its impact on visiting students. In the MSBE, students interact with, and operate, sophisticated simulators which demonstrate a range of medical situations. Visiting students comprised mainly high school students, who do not commonly visit science centers. They included Jewish and Arab students of diverse socioeconomic statuses. Data collection in this mixed‐method study comprised pre‐post open‐ended views and content questionnaires, a semantic difference survey and interviews. To scrutinize student learning and attitude change, we compared the visiting students with a comparison group who did not visit the MSBE. The MSBE enabled mainly collaborative and active/hands‐on learning that helped students visualize and experience abstract ideas and yielded a variety of learning outcomes. We present evidence that the students improved their attitudes toward biology and medicine and improved their understanding of biological principles related to the human body. Addressing both museum learning literature and literature on different types of scientific and health literacies, we highlight the value to student engagement and learning of this unique medical simulation learning environment.